Territorialidades em habitação de interesse social - Bitencourt Monteiro, Mg. Arq. Deyvid Aléx (Universidad Nacional del Litoral, 2019)
In social interest housing, expressions of deterritorialization can be manifested through modifications made by users in their housing units. Such modifications may occur based on users' cultural and subjective values. The main objective of this article is to evaluate the different territorialities by means of the identification of the changes made and intended and the permanence or not of the users of housing of social interest. As a case study, three projects belonging to the Integrated City Entrance Program (PIEC) were evaluated. As methodological procedures, the construction of a questionnaire, in-situ observations, sample planning, data collection and analysis was performed. Statistical descriptive techniques were used to analyze the data. Among the main contributions of this research is the identification and categorization of the different forms of modifications made and desired in the housing units investigated. Also, the territorialities analyzed together with the percentage of permanence of the residents indicated possible means for the monitoring of the results obtained by the Brazilian housing programs.